Peranan Lembaga Kepolisian Dalam Pemberantasan Penyalahgunaan Minuman Beralkohol Di Kalangan Pemuda Yang Mengganggu Ketertiban Umum ( Studi Kasus Di Wilayah Hukum Kepolisian Sektor Maulafa ) - Theresia Dwierlangga Rosari Mole; Rudepel Petrus Leo; Ngongo Dede (Journal of Innovative and Creativity (Joecy), 2026)
Alcohol abuse among young people has become one of the major factors contributing to public order disturbances and criminal offences within the jurisdiction of the Maulafa Sector Police, Kupang City. This condition requires the police to play an active role in maintaining public security and order through effective countermeasures. This study aims to analyze the effectiveness of the measures implemented by the Maulafa Sector Police in maintaining public order related to alcohol abuse among youths and to identify the obstacles encountered in their implementation. This research employed an empirical legal method with a qualitative approach. Data were collected through interviews, observations, documentation, and literature studies, and were analyzed using descriptive qualitative methods. The findings reveal that the Maulafa Sector Police have implemented pre-emptive measures through legal counseling and public education, preventive measures through routine patrols, inspections of illegal alcoholic beverages, and monitoring of vulnerable locations, as well as repressive measures through law enforcement against offenders whose crimes were associated with alcohol abuse. These efforts have been reasonably effective in reducing public order disturbances; however, their effectiveness has not yet reached an optimal level due to limited personnel and facilities, low public legal awareness, and socio-cultural factors that continue to tolerate alcohol consumption. Therefore, stronger collaboration among the police, local government, community leaders, families, and the public is essential to improve the prevention of alcohol abuse among young people.